Optimizing Digital Literacy and Traditional Games to Reduce the Impact of Online Games - Maharani Fatima Gandasari; Putra Sastaman B; Ghana Firsta Yosika; Rubiyatno; Rahmat Putra Perdana; Touvan Juni Samodra; Eka Supriatna (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of digital technology has had a significant impact on the behavior of children and adolescents, including increasing addiction to online games. This phenomenon causes various problems such as decreased academic achievement, impaired social interaction, and physical and mental health problems. The purpose of this article is to examine strategies for reducing the negative impacts of online games through optimizing digital literacy and preserving traditional games. Digital literacy plays an important role in equipping children, parents, and educators with the knowledge and skills to use technology wisely and responsibly. Meanwhile, traditional games can be an educational and recreational alternative that encourages physical activity, social interaction, and strengthening local cultural values. The combination of these two approaches is expected to create a balance in the use of technology while strengthening the cultural identity of the younger generation. Online games have become part of the lives of modern children and adolescents, but excessive use without supervision has a negative impact on mental, social, and academic health. This community service activity aims to educate elementary school students about healthy digital literacy and reintroduce traditional games as an alternative to fun physical and social activities. The implementation method includes socialization, training, and practice of traditional games at SDN 17 Sungai Raya in West Kalimantan. The results show an increase in students' understanding of the wise use of gadgets and high enthusiasm in participating in traditional games. The conclusion of this activity is that collaboration between digital literacy and local cultural preservation can reduce dependence on online games